Perpustakaan dan Masyarakat Informasi - Ernawati . (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2016)
Advances of information technology is currently grow very rapidly becomean information seeker nearly to information sources it needs. A Library asone of the information center, is expected to follow or adjust to the progress ofinformation technology develop at this time, in present information neededby user. The existence of an information society is very important in utilizingthe source of information provided by the library. In the informationsociety, the awareness of libraries is huge because they think that they needfor information is just as important as the needs of others. In their daily lifeneed information. In the information society, economic, and technologicalglobalization brings libraries not only related to education, but librariesalso linked to social systems. The role of libraries in the information societyis very influential because in general the library is a source of information,education, research, preservation, and preserving the cultural treasures ofthe nation as well as a healthy, cheap, and useful recreation place. Thus,libraries and communities are interconnected with one another or it canbe said that the existence of libraries in the midst of society because of acausal relationship.